The dominant caste and other essays - Srinivas, Mysore Narasimhachar (Delhi Oxford University Press, 1987)
Case studies of Rampura Village in Karnataka.
Keywords: Caste -- India -- Case studies; Caste -- India -- Rampura -- Case studies; Rampura (India) -- Social conditions -- Case studies; India -- Social conditions -- Case studies